The Use of Slang in Teenagers' Facebook Pages - Pewpalaplow, Chomphoonuch; Pansila, Ananya; Thamdecho, Hanun; Chanaroke, Ubonrat (Journal of English Language and Linguistics, 2023)
The purpose of this study was to determine the percentage of teenagers using Facebook slang and to find out the types of words displayed on Facebook. To study the vocabulary and sentence patterns of slang used by teenagers on Facebook, researchers used the slang quiz as a tool to find answers to research questions. The researchers then analyzed teen slang to determine the percentage of teenagers using Facebook slang and to find out the types of Facebook slang. The study was found that the test measured a basic understanding of Facebook slang. It can be seen that the sample group had a moderate level of knowledge of Facebook slang; the sample saw the slang on the Facebook page being popular at a high level; the sample group had a moderate level of understanding of Facebook slang; and the sample group used slang in their Facebook communication with friends or acquaintances at a low level.